2005
DOI: 10.1159/000089175
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Effect in Bladder Cancer between N-Acetyltransferase 2 Genotype and Alcohol Drinking

Abstract: Cigarette smoking, aromatic amines and ionizing radiation are known carcinogens of bladder cancer. NAT2 genotype might play a role in bladder cancer carcinogenesis. This hospital-based, case-control study was conducted in Kaohsiung, Taiwan, which neighbors the high incidence region of bladder cancer in the black-foot disease area. A total of 103 cases with diagnosed bladder cancer were collected. For each case, 1 control was selected from the same hospital. A structured questionnaire was applied for all cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Upon closer examination, sixteen articles did not provide sufficient information to estimate a summary odds ratio and its 95% confidence intervals [17][18][19][20][21][22], or a summary odds ratio adjusted for at least age, sex and smoking [23][24][25][26][27][28][29][30][31][32]. The remaining 19 articles [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] were chosen for detailed review.…”
Section: Resultsmentioning
confidence: 99%
“…Upon closer examination, sixteen articles did not provide sufficient information to estimate a summary odds ratio and its 95% confidence intervals [17][18][19][20][21][22], or a summary odds ratio adjusted for at least age, sex and smoking [23][24][25][26][27][28][29][30][31][32]. The remaining 19 articles [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] were chosen for detailed review.…”
Section: Resultsmentioning
confidence: 99%
“…However, the homozygotes of minor allele of NAT2 (rs1799930) SNP was associated with an increased risk of breast cancer among premenopausal (OR 2.70, 95% CI 1.20-6.07), although the number of the subjects were limited. Lu et al [23] showed an interaction effect in bladder cancer between NAT2 polymorphism and alcohol drinking. In addition, Rodrigo et al [24] reported that NAT2 activity may be a factor that determines the risk of developing alcoholic liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21][22] Furthermore, one study from Southern Taiwan revealed a lower frequency of the NAT2 fast acetylator genotype (54.3 percent, 76/103). 23 Thus, the analysis of NAT2 genetic polymorphisms in the cancer-free control population of this study may reflect the distribution of NAT2 genotypes in the Taiwanese population living in different geographic areas. Although, the frequency of NAT2 fast acetylator genotypes in the cancer-free control population was relatively lower than those of studies conducted in Northern Taiwan, the frequency of NAT2 fast acetylator genotype in this study was relatively comparable to most Taiwanese studies.…”
Section: Discussionmentioning
confidence: 88%